Wharton’s Jelly Derived Mesenchymal Stem Cells: A Comparison Study in Preterm vs. Term Deliveries and in FBS vs. PRP vs Mesencult Culture Media - Gita Pratama (Journal of Global Pharma Technology, 2020)
Background: Use of human mesenchymal stem cells (MSCs) for therapy in the field of degenerative medicine has been extensively studied. One of the potential sources of MSC which is easily available is from the human umbilical cords Wharton’s jelly of the newborn baby. Wharton's jelly derived MSCs (WJ-MSCs) from full-term labor has been isolated and differentiated, but very limited data came from preterm labor. This study aimed to compare the proliferation and differentiation characteristics between human WJ-MSCs from preterm and term labor using xeno-free culture media, particularly platelet rich plasma (PRP). Methods: WJ-MSCs from preterm and term deliveries was cultured using culture medium supplemented with 10% PRP or MSC or FBS culture media. Cells were cultured until the fifth passages. Cumulative cell numbers and differentiation capacity of the MSCs was tested according to International Society for Cellular Therapy (ISCT) criteria. Results: The preterm WJ-MSCs grown in culture media is not significant differences with WJ-MSCs derived from full-term labor, but have higher number of cell populations. WJ-MSCs are able to differentiate into osteocyte, chondrocyte and adipocyte., and xeno-free media can be used to replace FBS. WJ J-MSCs from preterm labor can be used as a source for mesenchymal stem cells. Conclusion: WJ-MSCs collected from preterm samples to have a better proliferation rate compared to term samples, while possessing equal differentiation capacity. In addition, PRP can replace FBS as it a xeno-free material for WJ-MSCs production that required for regenerative medicine. Keywords: Mesenchymal stem cells, Wharton’s jelly, Preterm labor, Proliferation, Differentiation.